Pengaruh Daya Tarik Wisata Terhadap Keputusan Berkunjung Di Desa Tarabunga Kecamatan Tampahan Kabupaten Toba Tahun 2023 - Untung P Simanjuntak; Rusmauli Simbolon; Elvri Teresia Simbolon; Maringan Sinambela; Jupalman W. Simbolon (Universitas Katolik Widya Karya Malang, 2023)
Tourist attraction includes various aspects such as natural beauty, environmental cleanliness of tourist attractions, environmental coolness, interaction with local communities, available facilities, and location accessibility. While visiting decisions include factors that encourage individuals to choose a particular destination, such as personal motivation, social influence and preparation before visiting. Thus, tourist attractions should be developed as much as possible to encourage people to come visit it. The purpose of this study was to find out how the influence of tourist attraction on the decision to visit Tarabunga Village. The type of research used quantitative research. The data processing was obtained from questionnaire data collection data distributed to 50 respondents. The data analysis techniques used are simple regression analysis, correlation analysis, coefficient of determination and t test (hypothesis test). Based on the results of the analysis and discussion described in the previous chapter, the author draws several conclusions from the results of the analysis that based on the hypothesis proposed by the researcher, a t test was carried out and obtained the SPSS output showed a calculated t value of 0.961 with a Sig of 0.001. To determine the level of significance of the research model, the calculated t value is compared with the table t value. The calculated t value for the error degrees 5%(α=0.05)and df(n-k =50-2=48) is 1.677 which means that the calculated t (46.489) is greater than the table t 1.677 so that the influence of variable X on the decision to visit is significant. Based on the results of this analysis, the hypothesis that states the attractiveness of wsaita has a positive and significant effect on the decision to visit the tarabunga tourism village is empirically proven and acceptable.